LEGALITAS PENGGUNAAN VIRTUAL OFFICE SEBAGAI KANTOR ADVOKAT - Ni Kadek Ratna Jayanti (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2017)
Virtual office is a joint office equipped with physical facilities and human resources facilities. Virtual office is supported with internet facility, call center, receptionist, workspace, and technology-based meeting room. Advocates can use virtual office as an office in providing legal services to the public. In this study there are two problems that can be formulated that is 1) how is the legal relationship between the owner of a virtual office with an advocate who uses a virtual office as an advocate office? 2) How can a virtual office place be the domicile of an advocate’s office? This study is a normative legal research that examines the empty norm of virtual office. This condition will complicate the determination of domicile of a business entity. Legal material consists of primary legal materials and secondary legal materials collected through library studies. The analysis is done qualitatively. The legal relationship between a virtual office owner and an advocate who using a virtual office as an advocate’s office is based on a lease agreement. Virtual office agreement object used as an advocate’s office. The virtual office space may be the seat of an advocate's office. Legality of advocates is determined by individual qualifications. In Act No. 18 of 2003 on Advocates does not regulate the requirements of the advocate's office as the basis of legality as an advocate. The virtual office address can be used as the domicile of the advocate office. Virtual office adalah kantor yang bersama yang dilengkapi dengan fasilitas fisik dan fasilitas sumber daya manusia. Virtual office didukung dengan fasilitas internet, call centre, resepsionis, ruang kerja, dan ruang pertemuan berbasis teknologi. Advokat dapat menggunakan virtual office sebagai kantor dalam memberikan jasa hukum kepada masyarakat. Dalam penelitian ini ada dua permasalahan yang dapat dirumuskan yakni 1) bagaimanakah hubungan hukum antara pemilik virtual office dengan advokat yang menggunakan virtual office sebagai kantor advokat? 2) Bagaimanakah tempat kedudukan virtual office dapat menjadi tempat kedudukan kantor advokat? Penelitian ini merupakan penelitian yuridis normative yang mengkaji mengenai kekosongan norma mengenai virtual office. Kondisi ini akan menyulitkan legalitas penentuan domisili suatu badan usaha. Bahan hukum terdiri dari bahan hukum primer dan bahan hukum sekunder yang dikumpulkan melalui studi kepustakaan. Analisis dilakukan secara kualitatif. Hubungan hukum antara pemilik virtual office dengan advokat yang menggunakan virtual office sebagai kantor advokat didasarkan pada perjanjian sewa menyewa. Objek perjanjian virtual office yang digunakan sebagai kantor advokat. Tempat kedudukan virtual office dapat menjadi tempat kedudukan kantor advokat. Legalitas advokat ditentukan oleh kualifikasi individu. Dalam Undang-undang Nomor 18 tahun 2003 tentang Advokat tidak mengatur persyaratan mengenai kantor advokat sebagai dasar legalitas sebagai advokat. Alamat virtual office dapat digunakan sebagai domisili kantor advokat.